Walking time measures for evaluating OA of the knee - R. Marks (AOSIS, 1994)
This study assessed the test-retest reliability and the sensitivity of self-paced walking time measurements for evaluating the functional performance of persons with knee osteoarthritis (OA). The 13 m timed walking tests were carried out on two separate occasions over a six-week period for 10 patients using a standardised protocol. The same measurements were recorded also for three additional patients before and after a six-week quadriceps strength training regimen. As indicated by an intraclass correlation coefficient of 0.83 with no significant intersession test differences for the group (P=0.98), the gait measurements were reliable. However, despite marked increase in knee extensor strength and significant subjective improvements in walking time for the three experimental subjects were smaller than the error of measurement. The findings suggest that regardless of reliability, measurements of self-paced level walking time might not be sufficiently sensitive for evaluating longitudinal changes in functional performance in this patient population.